2015
DOI: 10.1371/journal.pone.0143013
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Interactions between Cisplatin and Two Histone Deacetylase Inhibitors in MCF7, T47D and MDA-MB-231 Human Breast Cancer Cell Lines – An Isobolographic Analysis

Abstract: Histone deacetylase inhibitors (HDIs) are promising anticancer drugs, which inhibit proliferation of a wide variety of cancer cells including breast carcinoma cells. In the present study, we investigated the influence of valproic acid (VPA) and suberoylanilide hydroxamic acid (SAHA, vorinostat), alone or in combination with cisplatin (CDDP) on proliferation, induction of apoptosis and cell cycle progression in MCF7, T47D and MDA-MB-231 human breast carcinoma cell lines. The type of interaction between HDIs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
87
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(103 citation statements)
references
References 59 publications
6
87
0
Order By: Relevance
“…This combination achieved to reduce the doses of the compounds and to be therapeutically beneficial for head and neck squamous cell carcinomas (26,73) and BC in vitro (74,75). This study also showed that in MDA-MB231 cells, the combination of the CDDP and VPA at the ratio of 1:1 induced antagonistic interactions, while CDDP and SAHA co-treatment induced synergistic interactions (71). According to the investigators, this could be explained by the fact that SAHA is a potent inhibitor of the HDAC6 activity compared to VPA (26).…”
Section: Hdac Inhibitors As Anti-cancer Agentsmentioning
confidence: 66%
See 4 more Smart Citations
“…This combination achieved to reduce the doses of the compounds and to be therapeutically beneficial for head and neck squamous cell carcinomas (26,73) and BC in vitro (74,75). This study also showed that in MDA-MB231 cells, the combination of the CDDP and VPA at the ratio of 1:1 induced antagonistic interactions, while CDDP and SAHA co-treatment induced synergistic interactions (71). According to the investigators, this could be explained by the fact that SAHA is a potent inhibitor of the HDAC6 activity compared to VPA (26).…”
Section: Hdac Inhibitors As Anti-cancer Agentsmentioning
confidence: 66%
“…Nevertheless, the majority of studies in the field of TNBC therapy tend to combine HDAC inhibitors with kinase inhibitors, autophagy inhibitors, antibiotics, chemotherapy, IR, or even two HDAC inhibitors treatment in order to enhance their efficacy against TNBC (47,69,71,84,115,123,153). In the majority of the studies, co-treatment of an HDAC inhibitor with another compound induced the inhibition of tumor growth and showed anti-proliferative effects (46,47,77,84,115,123,138,154).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations